2019
DOI: 10.1088/1757-899x/690/1/012005
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of the Undrained Shear Strength of Soft Clay Reinforced with Natural Fibre

Abstract: The term soil reinforcement is conventional since decades ago for the stabilization of soft ground such as of clay and peat. Numerous research has arisen in the utilization of natural fibres as the reinforcement materials. Cost reduction, increment of sustainability awareness and eco-friendly environment are some of the advantages when using natural fibres to stabilize soft ground. A research study was carried out to evaluate the strength of the soft soil when unreinforced and reinforced using natural fibres. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…The test showed that 0.5% fiber content resulted in an optimum increase [11]. Suffri, et al stated that coir fiber can increase the shear strength of soft clay with moderate plasticity in Brunei Darussalam [12]. Research Upadhyay and Singh showed an increase in shear strength with an increase in cohesion value by 34.7%…”
Section: Literature Reviewmentioning
confidence: 99%
“…The test showed that 0.5% fiber content resulted in an optimum increase [11]. Suffri, et al stated that coir fiber can increase the shear strength of soft clay with moderate plasticity in Brunei Darussalam [12]. Research Upadhyay and Singh showed an increase in shear strength with an increase in cohesion value by 34.7%…”
Section: Literature Reviewmentioning
confidence: 99%
“…The implementation of group-enclosed lime bottom ash columns enhanced clay soil shear strength. In his research, Suffri [13] used crushed coir fibres, and fibre incorporation affected the soil's undrained shear ability. Hong [14] evaluated the use of polypropylene and concluded that the parameters of the polypropylene column used to strengthen the sample significantly influenced the shear strength enhancement of the kaolin clay.…”
Section: Introductionmentioning
confidence: 99%
“…There have been many methods of soil improvement to enhance the physical and mechanical properties of clay. One of them is by providing soil reinforcement by inserting material into the soil to increase stability and reduce compressibility and lateral deformation [3]. One of the materials used is fiber mixed randomly into the soil.…”
Section: Introductionmentioning
confidence: 99%